Effect of anticancer drugs on production of transforming growth factor and expression of P53 and BCL-2 proteins by MCF-7 and T47D cell lines of human breast carcinoma - Stoika, R.S.; Yakymovych, I.A.; Kashchak, N.I.; Boyko, M.M.; Korynevska, A.V.; Klyuchyvska, O.Yu.; Shafranska, G.I.; Yakymovych, M.Ya.; Zhylchuk, V.Ye.; Kudryavets, Yu.Y.; Vorontsova, A.L. (Experimental Oncology, 2008)
Aim: To compare the capability of methotrexate, cisplatin, doxorubicine and vincristine to induce production of the transforming growth factor b1 (TGF- b1) in two cell lines — MCF-7 and T47D — of human breast carcinoma, as well as to study sensitivity of these cells to TGF- b1 and mentioned anticancer drugs. Materials and Methods: ELISA for detection of TGF- b content in conditioned culture media and Western-blot analysis of the proapoptotic p53 and antiapoptotic Bcl-2 proteins were applied. Results: t47d cells showing higher resistance to growth inhibiting effect of TGF- b1 were also refractory to cisplatin. There was no difference between MCF-7 and T47D cells in their sensitivity to methotrexate and doxorubicine, although T47D cells were more sensitive to vincristine. It was found that methotrexate and vincristine did not affect TGF- b1 production, while doxorubicine used at a dose of 1–100 ug/ml, significantly induced TGF- b1 production in both cell lines. p53 expression in T47D cells was higher than in MCF-7 cells where only doxorubicin induced strongly p53 expression. It should be noted, that Bcl-2 was better expressed in MCF-7 cells, while it was almost undetectable in T47D cells. Conclusion: In cells of human mammary carcinoma of MCF-7 and T47D lines doxorubicine, unlike vincristine and methotrexate, in dose depending manner induces production of TGF- b1. TGF- b1 production in carcinoma cells was associated with doxorubicine-mediated p53 expression in MCF-7 cells or high basal level of p53 in T47D cells. The cells of MCF-7 line were more sensitive to growth inhibition by exogenous TGF- b1 and to cisplatine action than T47D cells, but there was no difference between these cell lines in sensitivity to other anticancer drugs. Цель: провести сравнительный анализ способности метотрексата, цисплатина, доксорубицина и винкристина индуцировать
продукцию трансформирующего фактора роста (TФР)-β1
клетками рака молочной железы человека (линии MCF-7 и T47D),
а также исследовать чувствительность этих клеток к TФР-β1
и указанным противоопухолевым препаратам. Материалы
и методы: для определения содержания TФР-β1
в кондиционированной среде использовали иммуноферментный анализ.
Уровень белков p53 и Bcl-2 оценивали методом иммуноблоттинга. Результаты: клетки t47d, которые характеризовались
большей резистентностью к ростингибирующему действию TФР-β1
по сравнению с клетками MCF-7, оказались менее
чувствительными к цисплатину. Не выявлено различий между чувствительностью клеток MCF-7 и T47D к действию
метотрексата или доксорубицина, хотя клетки T47D были более чувствительными к винкристину. Метотрексат и винкристин
не влияли на продукцию TФР-β1
клетками MCF-7 и T47D, тогда как доксорубицин в дозе 1–100 мкг/мл существенно усиливал
продукцию TФР-β1
. Экспрессия белка p53 была более интенсивной в клетках T47D, по сравнению с клетками линии MCF-7,
и лишь в случае действия доксорубицина на клетки линии MCF-7 было выявлено значительное повышение его уровня. При
этом белок Bcl-2 был выявлен только в клетках MCF-7. Выводы: в клеточных линиях карциномы молочной железы человека
(MCF-7 и T47D) доксорубицин, в отличие от винкристина и метотрексата, дозозависимо индуцирует продукцию ТФР-β1
.
Индукция доксорубицином ТФР-β1
в клетках карцином ассоциирована с индукцией экспрессии р53 в клетках MCF-7
или повышенным базальным уровнем этого белка в клетках T47D. Клетки линии MCF-7, более чувствительные к ростингибирующему
действию экзогенного ТФР-β1
, чем клетки линии T47D, отличаются и более выраженной чувствительностью
к действию цисплатина, но не отличаются по чувствительности от других цитостатиков.